Keratoameloblastoma of the lower jaw: A rare challenging entity - Mina Moradi; Brad W Neville; Pouyan Aminishakib (Wolters Kluwer Medknow Publications, 2023)
Ameloblastoma is the second most common benign odontogenic tumor with various histopathologic features. Except for the unicystic type of ameloblastoma, the different microscopic patterns of this tumor show no significant correlation with long-term clinical behavior. During recent decades, additional challenging subtypes of ameloblastoma, including "Keratoameloblastoma" (KA), have been introduced in the literature. Here, we present a case of KA and discuss the important diagnostic microscopic features.